Complicações cirúrgicas associadas à Pieloureterostomia término-terminal com ligadura proximal do ureter nativo no transplante renal - Marinho Neto, Hernani De Oliveira [UNIFESP] (2019)
Objective: Pyeloureterostomy is not the preferred surgical technique during kidney transplantation and the need for concomitant ipsilateral nephrectomy is matter of concern. This retrospective analysis investigates the safety of the primary (P-PU) and secondary pyeloureterostomy (usually used to treat ureteroneocystostomy urinary leakage (UL-PU) or stenosis (US-PU)), without concomitant ipsilateral nephrectomy. Methods: From a cohort of 4215 kidney transplants performed from February 2010 to December 2014 we identified 495 where pyeloureterostomies with ligation of the native ureter but without nephrectomy were performed. Mean follow up time after transplantation was 33,8 months. Results: Transplanted patients mean age was 48.7 years and mean time on dialysis was 73.4 months. Chronic kidney disease was secondary to diabetes mellitus in 11.7%, autosomal dominant polycystic kidney disease (ADPKD) in 6% and neurogenic bladder in 2%. Of the 495 patients, 409 were P-PU, 76 UL-PU and 10 US-PU. The incidence of native ipsilateral complication requiring nephrectomy was 2% (n=10). ). Of 5 patients that had lumbar pain, 4 had ADPKD and one had hydronephrosis. Another 5 patients presented with fever, 3 had neurogenic bladder, and 4 were diagnosed with pyonephrosis. There were two graft losses and one death. Conclusion: This cohort analysis suggests that pyeloureterostomy with ligation of the native ureter without native nephrectomy is safe with low rate of ipsilateral nephrectomy. Caution and awareness are advised in patients with ADPKD and mainly in neurogenic and augmented bladders.